Campylobacter Spp. And Related Organisms in Poultry 2016
DOI: 10.1007/978-3-319-29907-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Non-jejuni/coli Campylobacter Species and Related Organisms in Poultry, and Their Relevance in Human and Animal Disease

Abstract: This chapter provides a survey of research on non-jejuni/coli Campylobacter spp. and related Arcobacter and Helicobacter species in poultry. The isolation and identification, clinical and veterinary relevance, and the pathogenicity and antibiotic sensitivity of the organisms are reviewed. Most studies done on poultry, especially chicken, have focused on C. jejuni and C. coli. Increasingly, other species, such as C. lari, C. upsaliensis, and C. avium, as well as species of the related genera Arcobacter and Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Reported evidences show that the smoker patients displayed a decrease of oxygen tension in the oral cavity, creating favorable environmental conditions in the periodontal pocket for the colonization of certain periodontopathogens (ABUSLEME et al, 2013;NICOLIĆ-JAKOBA et al, 2012). Therefore, it can be suggested that the oxygen conditions are important for C. gracilis, C. rectus and C. concisus and, in this oxygen reduced subgingival environment, they could increase the prevalence of C. gracilis for being a strict microaerobic microorganism (LASTOVICA, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported evidences show that the smoker patients displayed a decrease of oxygen tension in the oral cavity, creating favorable environmental conditions in the periodontal pocket for the colonization of certain periodontopathogens (ABUSLEME et al, 2013;NICOLIĆ-JAKOBA et al, 2012). Therefore, it can be suggested that the oxygen conditions are important for C. gracilis, C. rectus and C. concisus and, in this oxygen reduced subgingival environment, they could increase the prevalence of C. gracilis for being a strict microaerobic microorganism (LASTOVICA, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of periodontal diseases is multifactorial, where various factors such as host, environment and infectious agents are involved (PEREZ-CHAPARRO et al, 2014;HENNE et al, 2014;VARGAS SEGURA et al, 2015;SRINIVASAN, 2016;TOMAS et al, 2016;MEURIC et al, 2017). Campylobacter species have been isolated from humans and animals, being also associated with this disease (LASTOVICA, 2016). In humans, several species have been implicated as etiologic agents of periodontal disease (PEREZ-CHAPARRO et al, 2014, HENNE et al, 2014VARGAS SEGURA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After this time, Arcobacter isolation was performed using the membrane filtration technique 21 . Briefly, 100 mL of enrichment media were inoculated onto a sterile 0.45 µm pore size nitrocellulose membrane filter placed on the surface of non-selective blood agar plates, based on the Cape Town protocol 22 . Plates were left at room temperature for one hour.…”
mentioning
confidence: 99%
“…Lastovica et al [16] reported that C. concisus was the second species with a higher prevalence after C. jejuni. However, C. concisus has been isolated from diarrheic patients without other pathogenic microorganisms suggesting it to be an emerging cause of human gastroenteritis [16,57].…”
Section: Discussionmentioning
confidence: 99%
“…However, atypical Campylobacter species are gaining considerable attention as important human and animal pathogens [13][14][15]. Infections caused by Campylobacter are usually under-reported due to difficulties in isolation procedures [16,17]. For instance, it has been estimated that 40% of the bacteria from human faeces diagnosed through microscopy cannot be cultured in the laboratory [17].…”
Section: Introductionmentioning
confidence: 99%